Angiotensin receptor blockers and risk of myocardial infarction: meta-analyses and trial sequential analyses of 147 020 patients from randomised trials. (26th April 2011) - Bangalore, Sripal; Kumar, Sunil; Wetterslev, Jørn; Messerli, Franz H
Abstract : Objectives To evaluate the cardiovascular outcomes and other outcomes associated with angiotensin receptor blockers. Design Systematic review of randomised controlled trials with meta-analysis and trial sequential analysis (TSA). Data sources and study selection Pubmed, Embase, and CENTRAL searches for randomised clinical trials, until August 2010, of angiotensin receptor blockers compared with controls (placebo/active treatment) that enrolled at least 100 participants and had a follow-up of at least one year. Data extraction Myocardial infarction, death, cardiovascular death, angina pectoris, stroke, heart failure, and new onset diabetes. Results 37 randomised clinical trials included 147 020 participants and had a total follow-up of 485 166 patient years. When compared with controls (placebo/active treatment), placebo, or active treatment, angiotensin receptor blockers were not associated with an increase in the risk of myocardial infarction (relative risk 0.99, 95% confidence interval 0.92 to 1.07), death, cardiovascular death, or angina pectoris. Compared with controls, angiotensin receptor blockers were associated with a reduction in the risk of stroke (0.90, 0.84 to 0.98), heart failure (0.87, 0.81 to 0.93), and new onset diabetes (0.85, 0.78 to 0.93), with similar results when compared with placebo or with active treatment. Based on trial sequential analysis, there is no evidence even for an average 5.0-7.5% (upper confidence interval 5-11%) relative increase in myocardial infarction (absolute increase of 0.3%), death, or cardiovascular death with firm evidence for relative risk reduction of stroke (at least 1%, average 10%) (compared with placebo only), heart failure (at least 5%, average 10%), and new onset diabetes (at least 4%, average 10%) with angiotensin receptor blockers compared with controls. Conclusions This large and comprehensive analysis produced firm evidence to refute the hypothesis that angiotensin receptor blockers increase the risk of myocardial infarction (ruling out even a 0.3% absolute increase). Compared with controls, angiotensin receptor blockers reduce the risk of stroke, heart failure, and new onset diabetes.